Macromedia Fireworks 4: Illustrated Essentials - Johnson, Steven (Boston Course Technology, 2001)
Macromedia Fireworks 4: Illustrated Essentials. This book is a member of illustrateds Multimedia Tools series. These books teach students how to create text, grafics, video, animations, and sound for use in print publications, CD-ROM products, and Web-based applications.